Introduction and Establishment of SARS-CoV-2 Gamma Variant in New York City in Early 2021. (30th June 2022) - Vasylyeva, Tetyana I; Fang, Courtney E; Su, Michelle; Havens, Jennifer L; Parker, Edyth; Wang, Jade C; Zeller, Mark; Yakovleva, Anna; Hassler, Gabriel W; Chowdhury, Moinuddin A; Andersen, Kristian G; Hughes, Scott; et al.
Abstract: Background: Monitoring the emergence and spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants is an important public health objective. We investigated how the Gamma variant was established in New York City (NYC) in early 2021 in the presence of travel restrictions that aimed to prevent viral spread from Brazil, the country where the variant was first identified. Methods: We performed phylogeographic analysis on 15 967 Gamma sequences sampled between 10 March and 1 May 2021, to identify geographic sources of Gamma lineages introduced into NYC. We identified locally circulating Gamma transmission clusters and inferred the timing of their establishment in NYC. Results: We identified 16 phylogenetically distinct Gamma clusters established in NYC (cluster sizes ranged 2–108 genomes); most of them were introduced from Florida and Illinois and only 1 directly from Brazil. By the time the first Gamma case was reported by genomic surveillance in NYC on 10 March, the majority (57%) of circulating Gamma lineages had already been established in the city for at least 2 weeks. Conclusions: Although travel from Brazil to the United States was restricted from May 2020 through the end of the study period, this restriction did not prevent Gamma from becoming established in NYC as most introductions occurred from domestic locations. Abstract : Even though international travel restrictions between the United States and Brazil, the country where Gamma variant was first detected, were in place since May 2020, they did not prevent the lineage from establishing in New York City in early 2021.